2021
DOI: 10.1002/cam4.4139
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of stereotactic magnetic resonance image‐guided adaptive radiotherapy for primary and metastatic tumors in the abdomen and pelvis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The study found that adaptive frequency was reduced, accounting for just 14% of all treatment sessions. Additionally, the study indicated positive outcomes in terms of local control and progression-free survival, with limited occurrence of toxicities [ 65 ].…”
Section: Clinical Results Of Artmentioning
confidence: 99%
“…The study found that adaptive frequency was reduced, accounting for just 14% of all treatment sessions. Additionally, the study indicated positive outcomes in terms of local control and progression-free survival, with limited occurrence of toxicities [ 65 ].…”
Section: Clinical Results Of Artmentioning
confidence: 99%
“…retrospectively analyzed SBRT of Primary and metastatic tumors and reported a local control after 1 year of 87% an after 2 years 71%. In case of lesions treated with BED >=100 a local control after 2 years of 96% was shown ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRI-Linac experience has shown that the addition of MRI-guidance has enabled safe dose escalation in abdominal cancers with excellent early clinical outcomes [11,61]. The ability of MRI-guided adaptive radiotherapy to improve tumour coverage or avoid a normal organ overdose that would have occurred due to anatomical variation has also been shown in abdominal SABR for primary or oligometastatic abdominal cancers [56,62]. Henke et al showed that MRI-guidance for primary or oligometastatic abdominal cancers was able to achieve dose escalation in 20%, improve tumour coverage in 65%, and reverse a normal organ overdose in 75% of fractions.…”
Section: Mri-guided Proton Therapy For Improving Dose-escalationmentioning
confidence: 99%